Social Media in Enterprises in the Czech Republic - Kasparova, Eva (International Journal of Engineering and Technology, 2018)
Social media play an important role in the present business practice. Enterprises increase their usage of social media to accomplish various business objectives. Many companies are not only aware of the importance of social media in the contemporary economic practice but also perceive them as a competitive advantage. Social media expand the space for mutual communication both inside and outside an enterprise. Through social media, businesses can build, expand and consolidate social networks of relationships that are necessary to achieve the set goals. The paper focuses on the importance of social media in business practice and the use of social media by enterprises in the Czech Republic.Â